The conception of religious experience in the work of Mircea EliadeThe sacred and the profane (مجلة إحالات, 2026)
In his masterpiece The Sacred and the Profane, Eliade exposes us to the problematic of the sacred / profane and of the religious man in relation to his sacred cosmos. The author offers us the opportunity to go back and delve into the history of beliefs in primitive societies. His technique focuses on the sacred element as a means of showing his vision which includes not only thepalpable, but also what is universal. In addition, his problematic on the primitive sacred is a catalystthat highlights the manifestation of the universal sacred. We ask ourselves: How does the author interpret the religious experience through the sacred / secular duality?